NLRP3 inflammasome inhibition protects against intracranial aneurysm rupture and alters the phenotype of infiltrating macrophages - Dodd, William S.; Patel, Devan; Motwani, Kartik; Lucke-Wold, Brandon; Hosaka, Koji; Hoh, Brian L. (Frontiers in Stroke, 2023)
Background Aneurysmal subarachnoid hemorrhage is a devastating cerebrovascular disease associated with high morbidity and mortality. Macrophage-mediated mural inflammation is a key pathogenic component contributing to aneurysm rupture. Objective To investigate the effect of pharmacological inhibition of the NLRP3 inflammasome on aneurysm rupture. Methods Cerebral aneurysms were induced in C57BL/6 mice with a combination of hypertension and an intracranial dose of elastase. Mice were treated with either 40 mg/kg of MCC950 or saline via intraperitoneal injections. Vascular tissue at the circle of Willis was harvested for analysis via immunofluorescent microscopy or qPCR. Results NLRP3+ cells are more common in the aneurysm tissue compared to the normal cerebral vasculature. The mRNA expression of the downstream NLRP3 pathway components caspase-1, IL-1β, and GSDMD is also increased in the aneurysm tissue compared to healthy vessels. There was no difference in the aneurysm formation rate between MCC950- and vehicle-treated mice; however, MCC950 treatment significantly reduced aneurysm rupture rate. There was no difference in systemic blood pressure between both groups. MCC950 treatment also extended the symptom-free survival of mice after aneurysm induction. Mechanistically, NLRP3 inhibition decreased the phenotype polarization of infiltrating macrophages without affecting the total number of macrophages in the vessel wall. Conclusions Our results indicate that the NLRP3 inflammasome contributes to aneurysm rupture and macrophage polarization within the vessel wall. The NLRP3 pathway is a promising therapeutic target for the development of therapeutics to prevent aneurysmal hemorrhagic stroke.